Investigasi Experimental Jumlah Sudu Dan Kecepatan Angin Terhadap Performa Turbin Savonius Tipe S - Didik Sugiono; Shultoni Mahardika; Aini Lostari; Novi Indah Riani; Umi Kulsum; Baharuddin Putra Pamungkas (CV. IRA PUBLISHING, 2026)
Wind energy is a potential renewable energy source in Indonesia, but the relatively low wind speed requires efficient turbine technology. The Savonius turbine has become an alternative choice for generating electrical energy. This research aims to determine the performance of the Savonius type-S turbine with blade numbers of 3, 5, and 7 at different wind speeds. The method used was an experiment conducted in a laboratory-scale wind tunnel simulator, with testing conducted across three blade configurations at wind speeds of 6, 7, and 8 m/s. The research results show that the 3-blade turbine achieves optimal torque at all wind speeds, with a maximum of 0.24 Nm at 8 m/s. The maximum wind power is obtained with the 7-blade turbine, reaching 167 watts at 8 m/s. The optimal turbine power also occurs with the 3-blade configuration, with the highest value being 10.30 watts at 8 m/s. The highest turbine efficiency is achieved by the 7-blade turbine, which is 31.85% at 8 m/s. Based on these results, it is concluded that the number of blades affects the performance characteristics of the Savonius type-S turbine. The 3-blade configuration produces the best torque and turbine power, while the 7-blade configuration excels in wind power and efficiency.